Express q as a function of p, given that one root of x^2 + px + q = 0 is twice the other.

Printable View

- Mar 27th 2007, 01:52 PMceasar_19134Express q as a function...
Express q as a function of p, given that one root of x^2 + px + q = 0 is twice the other.

- Mar 27th 2007, 06:31 PMtopsquark
First find the roots:

x = [-p (+/-) sqrt{p^2 - 4q}]/2

So we know that x(+) = 2*x(-) (since x(+) must be the larger of the two).

So:

[-p + sqrt{p^2 - 4q}]/2 = 2*[-p - sqrt{p^2 - 4q}]/2

-p + sqrt{p^2 - 4q} = 2*[-p - sqrt{p^2 - 4q}]

-p + sqrt{p^2 - 4q} = -2*p - 2*sqrt{p^2 - 4q}

3*sqrt{p^2 - 4q} = -p <-- Square both sides.

9*(p^2 - 4q) = p^2

8p^2 - 36q = 0

2p^2 - 9q = 0

q = (2/9)p^2

I'll leave it to you to check that this answer is correct. (Squaring both sides of an equation occasionally introduces "solutions" that aren't correct, so you always need to check you answer.)

-Dan